VD_FINDINFO PPD 11/14 - 2/2016 vom 4. Januar 2016 - VD Tribunal cantonal (2016)
PRÉVOYANCE PROFESSIONNELLE, DIVORCE, PARTAGESENS GÉNÉRAL, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 CC, 22 al. 1 LFLP, 22 al. 2 LFLP, 7 OLP, 8a OLP